English-Based Learning Needs for Specific Purposes: An Analysis - Dessy Dwisusila; Havid Ardi; Hasanuddin WS (Edukasi: Jurnal Pendidikan, 2023)
AbstractThis research aimed to analyze the learning needs of English for students. The research method was used descriptively. Data collection was carried out using an online questionnaire via Google Forms to students to identify the needs and expectations of students in learning English. The number of samples was 50 students with the sampling technique using simple random sampling. The data analysis technique used descriptive quantitative. The results of the research showed that students of the Faculty of Science and Technology need to learn English which focuses on improving the four language skills, namely speaking, writing, listening, and reading. Students also hope to learn more English vocabulary related to their major because it is useful for them in the learning process of the subjects in their major. AbstrakPenelitian bertujuan untuk menganalisis kebutuhan pembelajaran bahasa Inggris bagi mahasiswa. Metode penelitian yang digunakan adalah penelitian deskriptif. Pengumpulan data dilakukan menggunakan kuesioner online melalui Google Forms kepada mahasiswa untuk mengidentifikasi kebutuhan dan harapan mahasiswa dalam pembelajaran bahasa Inggris. Jumlah sampel sebanyak 50 siswa dengan teknik pengambilan sampel menggunakan simple random sampling. Teknik analisis data yang digunakan adalah deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa mahasiswa Fakultas Sains dan Teknologi perlu mempelajari bahasa Inggris yang menitikberatkan pada peningkatan empat keterampilan berbahasa, yaitu berbicara, menulis, menyimak, dan membaca. Mahasiswa juga berharap untuk mempelajari lebih banyak kosakata bahasa Inggris yang berkaitan dengan jurusan karena berguna dalam proses pembelajaran mata kuliah di jurusan.